The effect of ambient temperature on the linear and nonlinear optical properties of truncated pyramidal-shaped InAs/GaAs quantum dot - MohammadAmin ZekavatFetrat; Mohammad Sabaeian; Ghahraman Solookinejad (Journal of Optoelectronical Nanostructures, 2021)
In this work, we calculated the energy levels of truncatedpyramidal-shaped InAs/GaAs QDs by using the finiteelement method by taking into account the ambienttemperature, because the system under study is notsymmetric, it is impossible to use the analytical methodto find the wave functions and energy levels of theelectron, and the finite element method is the solution tosuch problems. We showed that, with increasing thetemperature, the energy level of both the ground state andthe first excited state as well as S-to-P transitionfrequency increase. But the important point was that,increasing the temperature can shift linear and nonlinearsusceptibility graphs to higher frequencies. For example,for a pyramid with a base length of 25 nm and a height of5 nm, at zero and 500 K the maximum linear andnonlinear susceptibility values are shifted from 14terahertz to the 18 terahertz. This ability can be effectivein designing optical devices.